ASAS PUBLISITAS PADA HAK JAMINAN ATAS RESI GUDANG - Juliana Evawati (Universitas Airlangga, 2014)
The principle of publicity is closely related to property rights. Each of Guarantee Agency property rights in a way that is different. Loading Right Collateral Agreements on the warehouse receipt no later than a day after the date of imposition oft he rights agreement collateral to a second party warehouse receipt, which is the guarantee of the assignees hall notify the Registration Center Warehouse Receipt System in order to be recorded in the Register of Rights guarantee Imposition Top Warehouse Receipt. Then the Registration Center will issue a notice of the imposition of Rights Confirmation Proof Guarantee. The meaning of “notice” to sign if the birth registration of property rights on the Rights of the collateral for the warehouse receipt. This is done to avoid double guarantee and monitor the distribution of the warehouse receipt and provide legal certainty about th eparty entitled tothe goods in the event of injury promise.Key words: publicity,collateral,warehouse receipts.